DEPTH POSITIONING CONTROL OF A SPHERICAL UNDERWATER ROBOT VEHICLE (URV) - JABRALLA, ABDALLA ELTIGANI IBRAHIM (2017)
Underwater Robot Vehicles (URVs) are an underwater system that has its own power and controlled by an onboard computer. URV has been deployed to the numerous duties without human interventions, such as repairing subsea systems and installing networks for scientific research and data collection. In most of these applications, a stable motion is required for the URV.